Long-term efficacy and safety of incobotulinumtoxinA injections in patients with cervical dystonia. Issue 9 (18th May 2013) - Dressler, Dirk; Paus, Sebastian; Seitzinger, Andrea; Gebhardt, Bernd; Kupsch, Andreas
Abstract : Introduction: Previously, controlled trials have demonstrated the efficacy and tolerability of fixed doses of incobotulinumtoxinA (Xeomin, NT 201, botulinum toxin type A free from complexing proteins) to treat cervical dystonia (CD). To explore the clinical relevance of these findings, this study evaluated long-term use of flexible dosing regimens of incobotulinumtoxinA in a setting close to real-life clinical practice. Methods: Patients with CD received five injection sessions of incobotulinumtoxinA using flexible intervals (10–24 weeks) and dosing (≤300 Units) based on patients' needs. Outcome measures included Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS), the Dystonia Discomfort Scale (DDS), Investigator Global Assessment of Efficacy (IGAE) and Patient Evaluation of Global Response (PEGR). Results: Of 76 patients enrolled (men: 34%; naïve to botulinum toxin: 25%), 64 completed the study, receiving treatment over a duration of 49.3–114.1 weeks (total maximum duration: 121 weeks). Mean TWSTRS-Total and DDS scores significantly improved from study baseline to 4 weeks after each injection session (ranges of improvement: TWSTRS-Total: −11.7 to −14.3; DDS: −20.2 to −23.0). Up to 81.6% of investigators rated the efficacy as 'good' or 'very good' (IGAE) and up to 78.9% of patients rated the treatment response as 'improved' (PEGR). The most common adverse events were dysphagia, nasopharyngitis and headache. Conclusions: In this long-term study, incobotulinumtoxinA was administered using more flexible dosing regimens than those permitted in previous controlled trials. Repeated injections of highly purified incobotulinumtoxinA are effective and well tolerated for the treatment of CD in a setting close to real-life clinical practice.